Message from the Chief Executive Officer: My time as the Nurses Specialized in Wound, Ostomy and Continence Canada Chief Executive Officer: Nothing short of a privilege - Harley, Catherine (Canadian Journal of Wound, Ostomy and Continence, 2026)
My Time as the Nurses Specialized in Wound, Ostomy and Continence Canada Chief Executive Officer: Nothing Short of a Privilege It has been a great honour and privilege to be a part of Nurses Specialized in Wound, Ostomy and Continence Canada (NSWOCC) for the past twenty-two years, a part of the International Skin Tear Advisory Panel (ISTAP) for ten years and a part of the Canadian Pressure Injury Advisory Panel (CPIAP) since its launch in 2021. Together, with many extraordinary volunteers and staff members, we have rebuilt, reinvented, strengthened, and modernized our association, our special interest groups and the way wound, ostomy and continence education is delivered. Looking back on my time at NSWOCC, we have confronted seemingly insurmountable business challenges, along with many surprise twists and turns. I’ve seen our teams navigate these hurdles and mountains in ways that have not only made NSWOCC a better association but also made all of us far stronger and closer. We have developed national standards, best practice recommendations, decision aids, achieved CNA certification, participated in research, launched a journal, strengthened opportunities for nurses, worked for better equality of care, built tools that delight our users, focused on improving outcomes for our patients, driven substantial value for our members, and endeavored to make NSWOCC an association where people belong. NSWOCC is a home and a family. As I look back on these achievements, I want to sincerely thank every single member, board director, core program leader and committee member, the staff, academic advisors, volunteers and Industry partners past and present, for your contributions which came in many ways. I’m tremendously grateful for all of the hard work and the many sacrifices you’ve made. We always endeavored to do the right thing for our members, our patients and our association. This has required the most impressive displays of teamwork, innovation, and resilience I’ve ever seen, and working with you has made my time as CEO nothing short of a privilege. I am now passing the baton over to Axelle Pellerin, your new NSWOCC CEO, knowing that NSWOCC is well prepared.